2019
DOI: 10.4081/pmc.2019.219
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic balloon dilatation of primary obstructive megaureter: method standardization and predictive prognostic factors

Abstract: The management of congenital primary obstructive megaureter (POM) is usually conservative, especially during the first year of life. Endoscopic high-pressure balloon dilatation (EHPBD) is indicated when symptoms, increasing dilatation and progressive renal damage are recorded, particularly in children younger than one year of age. We identified and described endoscopic prognostic factors predicting the success or failure of endoscopic dilatation. Thirty-eight patients (33 M;5 F) with POM from 2005-2018 were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…Out of 13 studies included, ten reported routinely using a double-J stent for three weeks to 3 months after HPBD [ 10 , 11 , 13 , 15 , 16 , 18 22 ]. Two authors [ 12 , 14 ] reported that a double-J was not inserted routinely. Faraj S et al [ 17 ] compared those with and without double-J after HPBD.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Out of 13 studies included, ten reported routinely using a double-J stent for three weeks to 3 months after HPBD [ 10 , 11 , 13 , 15 , 16 , 18 22 ]. Two authors [ 12 , 14 ] reported that a double-J was not inserted routinely. Faraj S et al [ 17 ] compared those with and without double-J after HPBD.…”
Section: Resultsmentioning
confidence: 99%
“…Out of the 13 studies, five [ 10 , 14 , 19 21 ] reported using a single perioperative antibiotics prophylaxis only, while five [ 13 , 15 , 17 , 18 , 22 ] reported continuing antibiotics as chemoprophylaxis after HPBD. Most used prophylaxis until the double- J stent was removed, while Casal Beloy et al [ 13 ] reported continuing antibiotics for only 5 days.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations